Online Module: Bibliometric Analysis (1998–2023) - Pamungkas Wirasanty Dewi (Scientia Publica Media, 2024)
This study aims to analyze trends in the development of research or scientific publications, especially in topic development, keywords that frequently appear, articles that are most cited, institutions, and authors who are active and collaborate in developing online modules or web modules. The method used is bibliometric analysis with a database taken from Scopus from 1998 to 2023 in September 2023. From this search, 1434 articles were found related to online modules. Scopus data shows that the use and publication of online modules or web modules increased in 2021 and then decreased in 2023. BMC Medical Education, Mededportal The Journal of Teaching and Learning Resources, and Currents in Pharmacy Teaching and Learning are the top 3 journals that publish online modules or web modules. The institutions that publish the most online modules come from the US and Australia, including the University of Toronto, the University of Pittsburg, and the University of California, San Francisco. The most productive writers are Palermo with 341 articles, Jennifer N Stinson with 339 articles, and Nader Francis with 154 articles. The country with the highest number of articles, namely 597 articles, is the US. Publications regarding this online module are mostly in the fields of medicine, social sciences, nursing, computer science, medicine, and pharmacy. Likewise, institutions, journals, and authors who publish online modules or web modules are mostly in the fields of medicine and pharmacy. In the field of education and natural science itself, especially in the field of chemistry, it is still very rare to find. This can be used as a reference for current and future research trends.